2008
DOI: 10.1002/meet.2008.14504503118
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of image users across disciplines: A model of image needs, retrieval and use

Abstract: This study investigates the image behaviors of twenty-four participants in four separate user groups (six in each group: archaeologists, architects, art historians and artists). These groups of participants were chosen due to their heavy reliance on images to perform their daily work routines. Two of the image user groups, archaeologists and art historians, are expected to need images for pedagogical and research purposes while the two remaining groups, architects and artists, are believed to need images for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…The research presented here is part of a larger study which sought to identify, describe and understand the human behaviors, thoughts and beliefs surrounding image needs, retrieval and use among archaeologists, architects, art historians and artists (Beaudoin, 2009). The limited research in the area of image users' behaviors meant this study was exploratory in nature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research presented here is part of a larger study which sought to identify, describe and understand the human behaviors, thoughts and beliefs surrounding image needs, retrieval and use among archaeologists, architects, art historians and artists (Beaudoin, 2009). The limited research in the area of image users' behaviors meant this study was exploratory in nature.…”
Section: Methodsmentioning
confidence: 99%
“…The artists were found to be the most dependent on analog materials. See the chapter on image retrieval in Beaudoin (2009) for a discussion of the resources used by artists and how these were found to differ from those of the other participant groups.…”
Section: Notesmentioning
confidence: 96%
“…The interviewees were specifically asked if they used Google Scholar for finding papers and the majority answered that they did not. When they knew that they were looking for papers, they used medical databases, and particularly PubMed [4] to find relevant literature. Often images were found as a by-product of paper searching.…”
Section: Articlesmentioning
confidence: 99%
“…These findings were reiterated by Hemmig (2009) who noted that books, magazines, photographs, as well as digital images, were used by artists as the main image resources to satisfy their visual information needs. Beaudoin (2009) examined the image resources used by 20 participants, including archaeologists, architects, art historians and artists. The findings of the study revealed that participants used various kinds of image resources, including books, non-digital image libraries, magazines, museums, image databases, personal collections, and web sites.…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct studies informed the methodology: research by Beaudoin (2009) that identified categories of both users and questions around usage was incorporated, and the ultimate use categories suggested by Chung and Yoon (2011) to compare against those used in this research. Researchers used data extracted via recorded system logs that are part of the statistics feature of the digital library.…”
Section: Subjects -Responses From 917 Users Of An Open Access Digitalmentioning
confidence: 99%